An Algorithm for Simulation of Forest Management Decisions in the Global Forest Model - Gusti, M.I. (Штучний інтелект, 2010)
An algorithm for decision making on forest management in the Global Forest Model (G4M) is developed. The algorithm provides harvesting of a specified amount of wood in countries. Adequateness of the algorithm is demonstrated on example of Ukraine, Poland, Byelorussia and Russia.